The treatment of chemotherapy-induced peripheral neuropathy: a review of current management options and a potential role for scrambler therapy - Aboumerhi, Hassan; Vucetic, Henry; Gruenzel, Andrew; Moftakhar, Bahar; Gupta, Mona; Rao, Santosh K.; Staudt, Michael D. (Frontiers in Pain Research, 2025)
Chemotherapy-induced peripheral neuropathy (CIPN) presents a growing medical and financial burden on patients and the healthcare system alike. This has been treated with conservative and interventional care limited by efficacy, side effects, and lack of coverage. As such, there is an unmet treatment need for effective non-invasive or minimally invasive therapies for the treatment of CIPN. Scrambler therapy (ST) is a peripheral, non-invasive neuromodulation technique, which uses transcutaneous electrical stimulation to modulate pain signals. ST has shown mixed results in clinical trials; while some patients report symptom relief, more robust evidence is required before it can be widely recommended. This review article outlines the burden of CIPN and the current state of treatment, including pharmacological and interventional therapies. The emerging data on ST and its role in treating CIPN is highlighted, including a review of published observational and randomized controlled trials. We also discuss the gaps and challenges ahead in establishing this therapy as a standard of care.